2012
DOI: 10.3389/fphar.2012.00102
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of Botulinum Neurotoxin Protease Domains

Abstract: Botulinum neurotoxins are most potent of all toxins. Their N-terminal light chain domain (Lc) translocates into peripheral cholinergic neurons to exert its endoproteolytic action leading to muscle paralysis. Therapeutic development against these toxins is a major challenge due to their in vitro and in vivo structural differences. Although three-dimensional structures and reaction mechanisms are very similar, the seven serotypes designated A through G vastly vary in their intracellular catalytic stability. To i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…This analysis is however complicated by the methodology used for the detection of the activity of these neurotoxins, which is based on antibodies recognizing the cleaved SNARE proteins. Indeed, this approach is highly dependent on variations in the enzymatic activity of the L chains of different serotypes, their efficiency of translocation into the cytoplasm, their post-translational modifications and the relative intracellular stability of both the L chain and the cleaved substrates, parameters for which our present understanding is very limited [6], [41], [61], [62].…”
Section: Discussionmentioning
confidence: 99%
“…This analysis is however complicated by the methodology used for the detection of the activity of these neurotoxins, which is based on antibodies recognizing the cleaved SNARE proteins. Indeed, this approach is highly dependent on variations in the enzymatic activity of the L chains of different serotypes, their efficiency of translocation into the cytoplasm, their post-translational modifications and the relative intracellular stability of both the L chain and the cleaved substrates, parameters for which our present understanding is very limited [6], [41], [61], [62].…”
Section: Discussionmentioning
confidence: 99%
“…(14) To probe whether or not 6 prevents BoNT/A’s phosphorylation, we screened the inhibitor against a panel of 50 kinases including Src at 20 μM (see the Supporting Information). Unfortunately, 6 presented no activity against all kinases examined.…”
Section: Resultsmentioning
confidence: 99%
“…(11) Furthermore, it has been suggested that the biologically relevant form of the LC enzyme is distinct from recombinant LCs used in current assays, due to cellular modifications by host proteins. (14)…”
Section: Introductionmentioning
confidence: 99%
“…One hypothesis is that the examined SFK inhibitors may be preventing the Src-mediated phosphorylation of BoNT LCs. Previous studies have reported that BoNT LCs are phosphorylated by Src kinase, and such phosphorylation events might be critical for toxins’ activities and stability (Ibanez et al 2004; Blanes-Mira et al 2001; Encinar et al 1998; Ferrer-Montiel et al 1996), but there are contradictions regarding the phosphorylation sites and their functional effects (Toth et al 2012). Additionally, it is not known if the LCs are phosphorylated in the physiological target of BoNTs, i.e., motor neurons.…”
Section: Discussionmentioning
confidence: 99%
“…However, our mechanistic understanding of the host signaling pathways involved in BoNT intoxication and/or recovery remains minimal. Some studies have suggested that BoNT activity depends on its phosphorylation by Src (Ibanez et al 2004; Blanes-Mira et al 2001; Encinar et al 1998; Ferrer-Montiel et al 1996; Toth et al 2012). Src family kinases (SFKs) play critical roles in many cellular functions in the nervous system, including the development and maintenance of neurons, synaptic plasticity, axon guidance, and neurotransmission (Ohnishi et al 2011).…”
Section: Introductionmentioning
confidence: 99%